Volumetric navigators for prospective motion correction and selective reacquisition in neuroanatomical MRI - Tisdall, M. Dylan; Hess, Aaron T.; Reuter, Martin; Meintjes, Ernesta M.; Fischl, Bruce; van der Kouwe, André J. W. (Magnetic resonance in medicine, 2012)
We introduce a novel method of prospectively compensating for subject motion in neuroanatomical imaging. Short three‐dimensional echo‐planar imaging volumetric navigators are embedded in a long three‐dimensional sequence, and the resulting image volumes are registered to provide an estimate of the subject's location in the scanner at a cost of less than 500 ms, ∼ 1% change in contrast, and ∼3% change in intensity. This time fits well into the existing gaps in sequences routinely used for neuroimaging, thus giving a motion‐corrected sequence with no extra time required. We also demonstrate motion‐driven selective reacquisition of k‐space to further compensate for subject motion. We perform multiple validation experiments to evaluate accuracy, navigator impact on tissue intensity/contrast, and the improvement in final output. The complete system operates without adding additional hardware to the scanner and requires no external calibration, making it suitable for high‐throughput environments. Magn Reson Med, 2012. © 2011 Wiley Periodicals, Inc.